Theory and Praxis, Theory and Practice, Practical Theory - Corentin Debailleul; Shimshon Bichler; Jonathan Nitzan (Review of Capital as Power, 2018)
In their paper `The CasP Project: Past, Present and Future', Shimshon Bichler and Jonathan Nitzan invite readers to engage critically with their theoretical framework, known as capital as power (CasP). This call for further research, reactions and critiques is the perfect occasion to raise a few questions that have grown in my mind in reading Nitzan and Bichler's work.
Keywords: P16; B14; 330; capital as power; capitalist mode of power; Marxism